Mesoporous titanium dioxide fiber reinforced aluminum-based composite material and preparation method thereof

By using mesoporous titanium dioxide fibers and high entropy oxide ceramic nanoparticle reinforced aluminum alloys, an aluminum-based composite material with high flexural strength, hardness and tensile strength was prepared, which solved the problem of insufficient mechanical properties of the materials in the prior art.

CN119876795APending Publication Date: 2025-04-25苏州创泰合金材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410929894.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-11
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to provide an effective mesoporous titanium dioxide fiber-reinforced aluminum-based composite material, and there is a lack of a method that can significantly improve the comprehensive mechanical properties of the material.

Method used

A composite material composed of 85-95% aluminum alloy and 5-15% mesoporous titanium dioxide fibers is prepared by ball milling uniform, pre-pressed green body and plasma discharge sintering technology. The surface of the mesoporous titanium dioxide fibers is loaded with high entropy oxide ceramic nanoparticles.

Benefits of technology

It significantly improves the flexural strength, hardness and tensile strength of the material, while maintaining a high elongation of break, and its comprehensive mechanical properties are better than traditional materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004939319740000201
    Figure BDA0004939319740000201
  • Figure BDA0004939319740000211
    Figure BDA0004939319740000211
Patent Text Reader

Abstract

The invention discloses a porous titanium dioxide fiber reinforced aluminum-based composite material, the aluminum-based composite material is composed of 85-95 wt% of aluminum alloy and 5-15 wt% of mesoporous titanium dioxide fibers, the mesoporous titanium dioxide fibers are mesoporous titanium dioxide fibers loaded with high-entropy oxide ceramic nanoparticles, the mesoporous fibers are short fibers, the mesoporous aperture is 20-60 nm, and the mesoporous titanium dioxide fibers are porous titanium dioxide fibers loaded with high-entropy oxide ceramic nanoparticles and short fibers loaded with high-entropy oxide ceramic nanoparticles and short fibers loaded with high-entropy oxide ceramic nanoparticles and short fibers loaded with high-entropy oxide ceramic nanoparticles. And the particle size range of the nanoparticles is 50-150nm. Mesopores are formed in the surface of the mesoporous fiber, so that the surface energy is high, the binding force between the mesoporous fiber and nanoparticles and an aluminum alloy matrix is high, the fiber toughness is good, the high-entropy oxide ceramic crystal structure is simple and has high strength and high hardness, and the comprehensive mechanical property of the alloy can be effectively improved through the mesoporous fiber and the high-entropy oxide ceramic crystal. And the short fibers are randomly distributed in the alloy matrix in an orientation manner, so that the material has isotropy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloys, and in particular to a mesoporous titanium dioxide fiber reinforced aluminum-based composite material. Background Art

[0002] Aluminum-based composites are high-performance composites with aluminum or aluminum alloy as the matrix and ceramics, metals or intermetallic compounds as the reinforcement phase. They combine the advantages of the matrix and the reinforcement phase, and have excellent properties such as low density, high specific strength, good electrical and thermal conductivity, low thermal expansion coefficient, high thermal stability, and good fatigue resistance and corrosion resistance. They are widely used in aerospace, automotive industry, electronic devices, mechanical engineering and other fields, and are also one of the hot research topics in metal-based composites. The reinforcement of aluminum-based composites can be continuous fibers, short fibers, whiskers or particles, and reinforcements of different forms can also be added in combination to obtain better performance. Common reinforcement particle materials include silicon carbide, aluminum oxide, boron nitride, etc. Intermetallic compounds such as Ni-Al, Fe-Al and Ti-Al are also used as reinforcement particles. Particle reinforcement has high specific strength, high specific modulus, low density and good high temperature performance, and has many advantages such as wear resistance, fatigue resistance, low thermal expansion coefficient and good thermal conductivity. Whisker reinforcements mainly include aluminum borate, magnesium borate, silicon carbide, aluminum oxide, etc., which have high strength, wear resistance, heat resistance, insulation, corrosion resistance, conductivity, wave absorption, vibration reduction, etc. Fiber reinforcements are represented by boron fiber, carbon fiber, silicon carbide fiber and aluminum oxide fiber, among which the short fibers are randomly distributed in the matrix, making the composite material show isotropic characteristics. The commonly used methods for preparing aluminum alloys and composite materials are mainly melt casting and powder metallurgy. With the deepening of research, the effect of developing new aluminum-based materials based on melt casting technology, such as improving purity, adjusting composition, changing heat treatment specifications, etc., has become smaller and smaller. The use of powder metallurgy technology can not only avoid material component segregation, but also improve solid solubility, obtain some aluminum alloys that cannot be produced by melt casting technology, and can refine the organization and improve its morphology and distribution characteristics. Compared with aluminum alloys with similar composition prepared by melt casting, aluminum alloys prepared by powder metallurgy have better physical, chemical and mechanical properties. Therefore, powder metallurgy has become one of the most widely used preparation methods for high-performance aluminum alloys and composite materials.

[0003] Technical problem to be solved: The technical problem to be solved by the present invention is to provide a mesoporous titanium dioxide fiber reinforced aluminum-based composite material.

[0004] Technical solution: A mesoporous titanium dioxide fiber reinforced aluminum-based composite material, wherein the aluminum-based composite material is composed of 85-95wt% aluminum alloy and 5-15wt% mesoporous titanium dioxide fiber. Preferably, the method for preparing the mesoporous titanium dioxide fiber reinforced aluminum-based composite material comprises the following steps: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. Place the green body into a plasma discharge sintering furnace, pressurize and evacuate, heat up for sintering and keep warm, take it out after the furnace cools to room temperature, and obtain a mesoporous titanium dioxide fiber reinforced aluminum-based composite material. Preferably, the sintering pressure in step S3 is 35-45 MPa, the sintering temperature is 550-600° C., and the holding time is 10-20 min. Preferably, the aluminum alloy consists of the following components in weight ratio: Zn: 5.5~6.0wt%; Mg: 2.2~2.8wt%; Cu: 1.0~1.8wt%; Si: 1.5~2.5wt%; Fe: ≤0.4wt%; Ti: ≤0.2wt%; the balance is Al. Preferably, the mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles. Preferably, the method for preparing the mesoporous titanium dioxide fiber comprises the following steps: S11. The ethanol solvent, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are prepared in proportion and stirred to obtain a precursor solution; S12. The precursor solution is loaded into a syringe, and the process parameters are adjusted for electrospinning to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 is calcined and kept warm to obtain mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles. Preferably, in step S11, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:8-12:10-12:2-3. Preferably, in step S22, the electrospinning voltage is 18-22 kV, the spinning solution flow rate is 0.8-1.2 mL / h, the receiving distance is 13-17 cm, and the drum speed is 45-55 r / min. Preferably, the calcination temperature in step S15 is 800-900° C., and the holding time is 1-2 hours. Preferably, the composition of the high entropy oxide ceramic nanoparticles is (Ni 0.15-0.25 Cr 0.15-0.25 Mg 0.15- 0.25 Co 0.15-0.25 Y 0.15-0.25 )3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm. Beneficial effects: Compared with the prior art, the present invention has the following characteristics: The aluminum-based composite material of the present invention is sintered by an aluminum alloy matrix and mesoporous titanium dioxide fibers, wherein the mesoporous titanium dioxide fibers are short fibers, and high entropy oxide ceramic nanoparticles are loaded on the surface. The fibers have good toughness, and the high entropy oxide ceramics have high strength and high hardness. The mesopores on the fiber surface make the two have a strong bonding force, which can effectively improve the comprehensive mechanical properties of the material. At the same time, the distribution of the short fibers in the alloy matrix has random orientation, which can keep the composite material isotropic. Oxide ceramic particles are commonly used reinforcements for aluminum-based composites, with high specific strength, high specific modulus, low density and good high-temperature performance. As reinforcements, they can significantly improve the strength and hardness of materials. Nano-sized oxide ceramic particles have a more significant effect on improving the performance of aluminum-based composites. A single type of oxide ceramic has limited improvement on the performance of composites, so the present invention introduces the concept of high entropy materials into ceramic particle reinforcements. High entropy materials are generally solid solution structural materials prepared from 5 or more different elements in equimolar or nearly equimolar ratios, with "cocktail" effect, hysteresis diffusion effect, lattice distortion effect and high entropy effect, etc., so they have a series of new excellent properties, mechanical properties, electromagnetic properties and catalytic properties are better than traditional materials, and as reinforcements for aluminum-based composites, they can further enable materials to obtain excellent performance. Metal oxides themselves have unique optical, electrical, magnetic and mechanical properties. Preparation into fiber reinforcements can improve the specific strength and specific modulus of aluminum-based composites, and enable materials to obtain excellent performance. They are also one of the commonly used reinforcements for aluminum-based composites, but the poor wettability and interface reaction problems between the two limit their application in composites. Preparing metal oxides into mesoporous fibers can give the material an ordered mesostructure, high specific surface area and unique pores, as well as large aspect ratio, self-support, low density and other characteristics. Among them, the high specific surface area and many pores can effectively increase the contact area between the matrix material and the fiber, enhance the bonding force between the two, and improve the mechanical properties of the composite material. Both nanoparticles and short fibers can be randomly oriented and distributed in the composite matrix, making the composite material is isotropic and improving the overall performance of the material. However, if the nanoparticles are too small, they are prone to agglomeration during the mixing process with aluminum alloy powder, resulting in uneven composition and structural defects. Loading nanoparticles on the surface of mesoporous fibers can effectively avoid the problem of nanoparticle agglomeration in the matrix. At the same time, the mesopores also give the nanoparticles and fibers a strong binding force, and the nanoparticles are not easy to fall off during the powder mixing process. Therefore, the particles and fibers can be evenly dispersed in the matrix, making the composition and structure of the material uniform and consistent, thereby obtaining stable performance. Compared with the prior art, the present invention has the following advantages and positive effects: The invention utilizes plasma discharge sintering technology to prepare aluminum-based composite materials, has simple process, fast sintering speed, good sintered body quality, and is conducive to industrial production. The present invention adds nanoparticles and short fibers as reinforcements in an aluminum alloy matrix. The nanoparticles and short fibers are randomly distributed in the matrix, so that the composite material exhibits isotropic characteristics. The present invention loads nanoparticles on the surface of short fibers, thereby avoiding the agglomeration problem of the nanoparticles when mixed with aluminum alloy powder, and enables the fibers and nanoparticles to be evenly dispersed in the aluminum alloy matrix. DETAILED DESCRIPTION In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. Specific preferred examples are as follows: Embodiment 1: A mesoporous titanium dioxide fiber reinforced aluminum-based composite material, the aluminum-based composite material consists of 85wt% aluminum alloy and 15wt% mesoporous titanium dioxide fiber; The preparation method of the mesoporous titanium dioxide fiber reinforced aluminum-based composite material comprises the following steps: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 45MPa, the sintering temperature is 600°C, the holding time is 10min, the furnace is cooled to room temperature and then taken out to obtain a mesoporous titanium dioxide fiber reinforced aluminum matrix composite material; The aluminum alloy is composed of the following components in weight ratio: Zn: 5.5wt%; Mg: 2.8wt%; Cu: 1.8wt%; Si: 1.5wt%; Fe: 0.4wt%; the balance is Al; The mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The preparation method of the mesoporous titanium dioxide fiber comprises the following steps: S11. The solvent ethanol, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are mixed and stirred uniformly, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:8:10:2 to obtain a precursor solution; S12. The precursor solution was loaded into a syringe for electrospinning at a voltage of 18 kV, a spinning solution flow rate of 0.8 mL / h, a receiving distance of 13 cm, and a drum speed of 45 r / min to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 was calcined and kept warm at a temperature of 800°C for 2 hours to obtain a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The composition of the high entropy oxide ceramic nanoparticles is (Ni 0.2 Cr 0.2 Mg 0.2 Co 0.2 Y 0.2 )3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm. Embodiment 2: A mesoporous titanium dioxide fiber reinforced aluminum-based composite material, the aluminum-based composite material consists of 90wt% aluminum alloy and 10wt% mesoporous titanium dioxide fiber; The preparation method of the mesoporous titanium dioxide fiber reinforced aluminum-based composite material comprises the following steps: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 45MPa, the sintering temperature is 600°C, the holding time is 10min, the furnace is cooled to room temperature and then taken out to obtain a mesoporous titanium dioxide fiber reinforced aluminum matrix composite material; The aluminum alloy is composed of the following components in weight ratio: Zn: 5.6wt%; Mg: 2.8wt%; Cu: 1.7wt%; Si: 1.5wt%; Fe: 0.1wt%; Ti: 0.2wt%; the balance is Al; The mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The preparation method of the mesoporous titanium dioxide fiber comprises the following steps: S11. The solvent ethanol, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are mixed and stirred uniformly, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:8:10:2 to obtain a precursor solution; S12. The precursor solution was loaded into a syringe for electrospinning at a voltage of 18 kV, a spinning solution flow rate of 0.8 mL / h, a receiving distance of 13 cm, and a drum speed of 45 r / min to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 was calcined and kept warm at a temperature of 800°C for 2 hours to obtain a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The composition of the high entropy oxide ceramic nanoparticles is (Ni 0.2 Cr 0.2 Mg 0.2 Co 0.2 Y 0.2 )3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm. Embodiment 3: A mesoporous titanium dioxide fiber reinforced aluminum-based composite material, the aluminum-based composite material consists of 95wt% aluminum alloy and 5wt% mesoporous titanium dioxide fiber; The preparation method of the mesoporous titanium dioxide fiber reinforced aluminum-based composite material comprises the following steps: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 45MPa, the sintering temperature is 600°C, the holding time is 10min, the furnace is cooled to room temperature and then taken out to obtain a mesoporous titanium dioxide fiber reinforced aluminum matrix composite material; The aluminum alloy is composed of the following components in weight ratio: Zn: 5.5wt%; Mg: 2.3wt%; Cu: 1.5wt%; Si: 1.7wt%; Fe: 0.2wt%; Ti: 0.1wt%; the balance is Al; The mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The preparation method of the mesoporous titanium dioxide fiber comprises the following steps: S11. The solvent ethanol, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are mixed and stirred uniformly, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:8:10:2 to obtain a precursor solution; S12. The precursor solution was loaded into a syringe for electrospinning at a voltage of 18 kV, a spinning solution flow rate of 0.8 mL / h, a receiving distance of 13 cm, and a drum speed of 45 r / min to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 was calcined and kept warm at a temperature of 800°C for 2 hours to obtain a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The composition of the high entropy oxide ceramic nanoparticles is (Ni 0.2 Cr 0.2 Mg 0.2 Co 0.2 Y 0.2 )3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm. Table 1 Effect of mesoporous titanium dioxide fiber content on the mechanical properties of composite materials name Bending strength / MPa Hardness / HV Tensile strength / MPa Elongation / % Fiber content / % Example 1 201 195 277 1.15 5 Example 2 212 218 303 1.17 10 Example 3 235 224 315 1.23 15 Comparative Example 1 189 192 260 1.10 20 Embodiment 4: A mesoporous titanium dioxide fiber reinforced aluminum-based composite material, the aluminum-based composite material consists of 85wt% aluminum alloy and 15wt% mesoporous titanium dioxide fiber; The preparation method of the mesoporous titanium dioxide fiber reinforced aluminum-based composite material comprises the following steps: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 40MPa, the sintering temperature is 575℃, the holding time is 15min, the furnace is cooled to room temperature and then taken out to obtain a mesoporous titanium dioxide fiber reinforced aluminum matrix composite material; The aluminum alloy is composed of the following components in weight ratio: Zn: 6.0wt%; Mg: 2.6wt%; Cu: 1.4wt%; Si: 1.7wt%; Fe: 0.2wt%; Ti: 0.2wt%; the balance is Al; The mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The preparation method of the mesoporous titanium dioxide fiber comprises the following steps: S11. The solvent ethanol, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are mixed and stirred uniformly, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:8:10:2 to obtain a precursor solution; S12. The precursor solution was loaded into a syringe for electrospinning at a voltage of 18 kV, a spinning solution flow rate of 0.8 mL / h, a receiving distance of 13 cm, and a drum speed of 45 r / min to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 was calcined and kept warm at a temperature of 800°C for 2 hours to obtain a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The composition of the high entropy oxide ceramic nanoparticles is (Ni 0.2 Cr 0.2 Mg 0.2 Co 0.2 Y 0.2 )3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm. Embodiment 5: A mesoporous titanium dioxide fiber reinforced aluminum-based composite material, the aluminum-based composite material consists of 85wt% aluminum alloy and 15wt% mesoporous titanium dioxide fiber; The preparation method of the mesoporous titanium dioxide fiber reinforced aluminum-based composite material comprises the following steps: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 35MPa, the sintering temperature is 550℃, the holding time is 20min, the furnace is cooled to room temperature and then taken out to obtain a mesoporous titanium dioxide fiber reinforced aluminum matrix composite material; The aluminum alloy is composed of the following components in weight ratio: Zn: 5.8wt%; Mg: 2.6wt%; Cu: 1.4wt%; Si: 2.0wt%; Fe: 0.3wt%; Ti: 0.2wt%; the balance is Al; The mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The preparation method of the mesoporous titanium dioxide fiber comprises the following steps: S11. The solvent ethanol, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are mixed and stirred uniformly, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:8:10:2 to obtain a precursor solution; S12. The precursor solution was loaded into a syringe for electrospinning at a voltage of 18 kV, a spinning solution flow rate of 0.8 mL / h, a receiving distance of 13 cm, and a drum speed of 45 r / min to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 was calcined and kept warm at a temperature of 800°C for 2 hours to obtain a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The composition of the high entropy oxide ceramic nanoparticles is (Ni 0.2 Cr 0.2 Mg 0.2 Co 0.2 Y0.2 )3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm. Table 2 Effect of different sintering temperatures on the mechanical properties of composite materials name Bending strength / MPa Hardness / HV Tensile strength / MPa Elongation / % Sintering temperature / ℃ Example 3 235 224 315 1.23 600 Example 4 230 210 297 1.18 575 Example 5 217 198 274 1.10 550 Comparative Example 2 184 181 275 1.12 650 Comparative Example 3 150 137 195 0.97 500 Embodiment 6: A mesoporous titanium dioxide fiber reinforced aluminum-based composite material, the aluminum-based composite material consists of 85wt% aluminum alloy and 15wt% mesoporous titanium dioxide fiber; The preparation method of the mesoporous titanium dioxide fiber reinforced aluminum-based composite material comprises the following steps: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 45MPa, the sintering temperature is 600°C, the holding time is 10min, the furnace is cooled to room temperature and then taken out to obtain a mesoporous titanium dioxide fiber reinforced aluminum matrix composite material; The aluminum alloy is composed of the following components in weight ratio: Zn: 6.0wt%; Mg: 2.3wt%; Cu: 1.2wt%; Si: 2.1wt%; Fe: 0.4wt%; Ti: 0.1wt%; the balance is Al; The mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The preparation method of the mesoporous titanium dioxide fiber comprises the following steps: S11. The solvent ethanol, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are mixed and stirred uniformly, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:10:11:2 to obtain a precursor solution; S12. The precursor solution was loaded into a syringe for electrospinning at a voltage of 20 kV, a spinning solution flow rate of 1.0 mL / h, a receiving distance of 15 cm, and a drum speed of 50 r / min to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 was calcined and kept warm at a temperature of 800°C for 2 hours to obtain a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The composition of the high entropy oxide ceramic nanoparticles is (Ni 0.2 Cr 0.2 Mg 0.2 Co 0.2 Y 0.2 )3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm. Embodiment 7: A mesoporous titanium dioxide fiber reinforced aluminum-based composite material, the aluminum-based composite material consists of 85wt% aluminum alloy and 15wt% mesoporous titanium dioxide fiber; The preparation method of the mesoporous titanium dioxide fiber reinforced aluminum-based composite material comprises the following steps: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 45MPa, the sintering temperature is 600°C, the holding time is 10min, the furnace is cooled to room temperature and then taken out to obtain a mesoporous titanium dioxide fiber reinforced aluminum matrix composite material; The aluminum alloy is composed of the following components in weight ratio: Zn: 5.9wt%; Mg: 2.4wt%; Cu: 1.2wt%; Si: 2.2wt%; Fe: 0.3wt%; Ti: 0.1wt%; the balance is Al; The mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The preparation method of the mesoporous titanium dioxide fiber comprises the following steps: S11. The solvent ethanol, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are mixed and stirred uniformly, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:12:12:3 to obtain a precursor solution; S12. The precursor solution was loaded into a syringe for electrospinning at a voltage of 20 kV, a spinning solution flow rate of 1.0 mL / h, a receiving distance of 15 cm, and a drum speed of 50 r / min to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 was calcined and kept warm at a temperature of 800°C for 2 hours to obtain a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The composition of the high entropy oxide ceramic nanoparticles is (Ni 0.2 Cr 0.2 Mg 0.2 Co 0.2 Y 0.2 )3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm. Embodiment 8: A mesoporous titanium dioxide fiber reinforced aluminum-based composite material, the aluminum-based composite material consists of 85wt% aluminum alloy and 15wt% mesoporous titanium dioxide fiber; The preparation method of the mesoporous titanium dioxide fiber reinforced aluminum-based composite material comprises the following steps: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 45MPa, the sintering temperature is 600°C, the holding time is 10min, the furnace is cooled to room temperature and then taken out to obtain a mesoporous titanium dioxide fiber reinforced aluminum matrix composite material; The aluminum alloy is composed of the following components in weight ratio: Zn: 5.8wt%; Mg: 2.5wt%; Cu: 1.2wt%; Si: 2.4wt%; Fe: 0.1wt%; Ti: 0.1wt%; the balance is Al; The mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The preparation method of the mesoporous titanium dioxide fiber comprises the following steps: S11. The solvent ethanol, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are mixed and stirred uniformly, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:10:11:2 to obtain a precursor solution; S12. The precursor solution was loaded into a syringe for electrospinning at a voltage of 20 kV, a spinning solution flow rate of 1.0 mL / h, a receiving distance of 15 cm, and a drum speed of 50 r / min to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 was calcined and kept warm at a temperature of 850°C for 1.5 h to obtain a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The composition of the high entropy oxide ceramic nanoparticles is (Ni 0.2 Cr 0.2 Mg 0.2 Co 0.2 Y 0.2 )3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm. Embodiment 9: A mesoporous titanium dioxide fiber reinforced aluminum-based composite material, the aluminum-based composite material consists of 85wt% aluminum alloy and 15wt% mesoporous titanium dioxide fiber; The preparation method of the mesoporous titanium dioxide fiber reinforced aluminum-based composite material comprises the following steps: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 45MPa, the sintering temperature is 600°C, the holding time is 10min, the furnace is cooled to room temperature and then taken out to obtain a mesoporous titanium dioxide fiber reinforced aluminum matrix composite material; The aluminum alloy is composed of the following components in weight ratio: Zn: 5.9wt%; Mg: 2.3wt%; Cu: 1.7wt%; Si: 1.8wt%; Fe: 0.2wt%; Ti: 0.1wt%; the balance is Al; The mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The preparation method of the mesoporous titanium dioxide fiber comprises the following steps: S11. The solvent ethanol, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are mixed and stirred uniformly, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:10:11:2 to obtain a precursor solution; S12. The precursor solution was loaded into a syringe for electrospinning at a voltage of 20 kV, a spinning solution flow rate of 1.0 mL / h, a receiving distance of 15 cm, and a drum speed of 50 r / min to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 was calcined and kept warm at a temperature of 900° C. for 1 h to obtain a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The composition of the high entropy oxide ceramic nanoparticles is (Ni 0.2 Cr 0.2 Mg 0.2 Co 0.2 Y 0.2 )3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm. Table 3 Effect of mesoporous titanium dioxide fiber preparation parameters on the mechanical properties of composites name Bending strength / MPa Hardness / HV Tensile strength / MPa Elongation / % Example 3 235 224 315 1.23 Example 6 244 237 331 1.27 Example 7 231 228 309 1.19 Example 8 257 248 343 1.31 Example 9 268 255 357 1.32 Comparative Example 4 186 190 263 1.12 Comparative Example 5 153 184 271 1.02 Comparative Example 6 160 205 251 0.97 Embodiment 10: A mesoporous titanium dioxide fiber reinforced aluminum-based composite material, the aluminum-based composite material consists of 85wt% aluminum alloy and 15wt% mesoporous titanium dioxide fiber; The preparation method of the mesoporous titanium dioxide fiber reinforced aluminum-based composite material comprises the following steps: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 45MPa, the sintering temperature is 600°C, the holding time is 10min, the furnace is cooled to room temperature and then taken out to obtain a mesoporous titanium dioxide fiber reinforced aluminum matrix composite material; The aluminum alloy is composed of the following components in weight ratio: Zn: 5.6wt%; Mg: 2.5wt%; Cu: 1.7wt%; Si: 1.5wt%; Fe: 0.2wt%; Ti: 0.2wt%; the balance is Al; The mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The preparation method of the mesoporous titanium dioxide fiber comprises the following steps: S11. The solvent ethanol, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are mixed and stirred uniformly, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:10:11:2 to obtain a precursor solution; S12. The precursor solution was loaded into a syringe for electrospinning at a voltage of 20 kV, a spinning solution flow rate of 1.0 mL / h, a receiving distance of 15 cm, and a drum speed of 50 r / min to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 was calcined and kept warm at a temperature of 900° C. for 1 h to obtain a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The composition of the high entropy oxide ceramic nanoparticles is (Ni 0.15 Cr 0.15 Mg 0.25 Co 0.25 Y 0.2 )3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm. Embodiment 11: A mesoporous titanium dioxide fiber reinforced aluminum-based composite material, the aluminum-based composite material consists of 85wt% aluminum alloy and 15wt% mesoporous titanium dioxide fiber; The preparation method of the mesoporous titanium dioxide fiber reinforced aluminum-based composite material comprises the following steps: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 45MPa, the sintering temperature is 600°C, the holding time is 10min, the furnace is cooled to room temperature and then taken out to obtain a mesoporous titanium dioxide fiber reinforced aluminum matrix composite material; The aluminum alloy is composed of the following components in weight ratio: Zn: 5.7wt%; Mg: 2.8wt%; Cu: 1.7wt%; Si: 2.0wt%; Fe: 0.3wt%; Ti: 0.2wt%; the balance is Al; The mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The preparation method of the mesoporous titanium dioxide fiber comprises the following steps: S11. The solvent ethanol, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are mixed and stirred uniformly, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:10:11:2 to obtain a precursor solution; S12. The precursor solution was loaded into a syringe for electrospinning at a voltage of 20 kV, a spinning solution flow rate of 1.0 mL / h, a receiving distance of 15 cm, and a drum speed of 50 r / min to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 was calcined and kept warm at a temperature of 900° C. for 1 h to obtain a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The composition of the high entropy oxide ceramic nanoparticles is (Ni 0.25 Cr 0.25 Mg 0.2 Co 0.15 Y 0.15 )3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm. Embodiment 12: A mesoporous titanium dioxide fiber reinforced aluminum-based composite material, the aluminum-based composite material consists of 85wt% aluminum alloy and 15wt% mesoporous titanium dioxide fiber; The preparation method of the mesoporous titanium dioxide fiber reinforced aluminum-based composite material comprises the following steps: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 45MPa, the sintering temperature is 600°C, the holding time is 10min, the furnace is cooled to room temperature and then taken out to obtain a mesoporous titanium dioxide fiber reinforced aluminum matrix composite material; The aluminum alloy is composed of the following components in weight ratio: Zn: 5.5wt%; Mg: 2.8wt%; Cu: 1.4wt%; Si: 2.0wt%; Fe: 0.1wt%; Ti: 0.2wt%; the balance is Al; The mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The preparation method of the mesoporous titanium dioxide fiber comprises the following steps: S11. The solvent ethanol, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are mixed and stirred uniformly, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:10:11:2 to obtain a precursor solution; S12. The precursor solution was loaded into a syringe for electrospinning at a voltage of 18 kV, a spinning solution flow rate of 0.8 mL / h, a receiving distance of 13 cm, and a drum speed of 45 r / min to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 was calcined and kept warm at a temperature of 900° C. for 1 h to obtain a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The composition of the high entropy oxide ceramic nanoparticles is (Ni 0.2 Cr 0.15 Mg 0.15 Co 0.25 Y 0.25 )3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm. To further illustrate the technical effect of the present invention, the present invention also provides a comparative example, which is as follows: Comparative Example 1: An aluminum-based composite material, the aluminum-based composite material consisting of 80wt% aluminum alloy and 20wt% mesoporous titanium dioxide fiber; The preparation method of the aluminum-based composite material comprises the following steps: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered, the sintering pressure is 45MPa, the sintering temperature is 600°C, the holding time is 10min, the furnace is cooled to room temperature and then taken out to obtain an aluminum-based composite material; The aluminum alloy is composed of the following components in weight ratio: Zn: 5.8wt%; Mg: 2.2wt%; Cu: 1.5wt%; Si: 1.5wt%; Fe: 0.2wt%; Ti: 0.2wt%; the balance is Al; The mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The preparation method of the mesoporous titanium dioxide fiber comprises the following steps: S11. The solvent ethanol, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are mixed and stirred uniformly, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:8:10:2 to obtain a precursor solution; S12. The precursor solution was loaded into a syringe for electrospinning at a voltage of 20 kV, a spinning solution flow rate of 1.0 mL / h, a receiving distance of 15 cm, and a drum speed of 50 r / min to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 was calcined and kept warm at a temperature of 800°C for 2 hours to obtain a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The composition of the high entropy oxide ceramic nanoparticles is (Ni 0.2 Cr 0.2 Mg 0.2 Co 0.2 Y 0.2)3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm. Comparative Example 2: An aluminum-based composite material, the aluminum-based composite material consisting of 85wt% aluminum alloy and 15wt% mesoporous titanium dioxide fiber; The preparation method of the aluminum-based composite material comprises the following steps: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered, the sintering pressure is 45MPa, the sintering temperature is 500°C, the holding time is 20min, the furnace is cooled to room temperature and then taken out to obtain an aluminum-based composite material; The aluminum alloy is composed of the following components in weight ratio: Zn: 5.6wt%; Mg: 2.5wt%; Cu: 1.7wt%; Si: 1.7wt%; Fe: 0.2wt%; Ti: 0.1wt%; the balance is Al; The mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The preparation method of the mesoporous titanium dioxide fiber comprises the following steps: S11. The solvent ethanol, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are mixed and stirred uniformly, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:10:11:2 to obtain a precursor solution; S12. The precursor solution was loaded into a syringe for electrospinning at a voltage of 20 kV, a spinning solution flow rate of 1.0 mL / h, a receiving distance of 15 cm, and a drum speed of 50 r / min to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 was calcined and kept warm at a temperature of 900° C. for 1 h to obtain a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The composition of the high entropy oxide ceramic nanoparticles is (Ni 0.2 Cr0.2 Mg 0.2 Co 0.2 Y 0.2 )3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm. Comparative Example 3: An aluminum-based composite material, the aluminum-based composite material consisting of 85wt% aluminum alloy and 15wt% mesoporous titanium dioxide fiber; The preparation method of the aluminum-based composite material comprises the following steps: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered, the sintering pressure is 35MPa, the sintering temperature is 650°C, the holding time is 10min, the furnace is cooled to room temperature and then taken out to obtain an aluminum-based composite material; The aluminum alloy is composed of the following components in weight ratio: Zn: 5.7wt%; Mg: 2.5wt%; Cu: 1.2wt%; Si: 1.7wt%; Fe: 0.3wt%; Ti: 0.1wt%; the balance is Al; The mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The preparation method of the mesoporous titanium dioxide fiber comprises the following steps: S11. The solvent ethanol, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are mixed and stirred uniformly, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:10:11:2 to obtain a precursor solution; S12. The precursor solution was loaded into a syringe for electrospinning at a voltage of 20 kV, a spinning solution flow rate of 1.0 mL / h, a receiving distance of 15 cm, and a drum speed of 50 r / min to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 was calcined and kept warm at a temperature of 900° C. for 1 h to obtain a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The composition of the high entropy oxide ceramic nanoparticles is (Ni 0.2 Cr 0.2 Mg 0.2 Co 0.2 Y 0.2 )3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm. Comparative Example 4: An aluminum-based composite material, the aluminum-based composite material consisting of 85wt% aluminum alloy and 15wt% mesoporous titanium dioxide fiber; The preparation method of the aluminum-based composite material comprises the following steps: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered, the sintering pressure is 45MPa, the sintering temperature is 600°C, the holding time is 10min, the furnace is cooled to room temperature and then taken out to obtain an aluminum-based composite material; The aluminum alloy is composed of the following components in weight ratio: Zn: 5.5wt%; Mg: 2.2wt%; Cu: 1.wt%; Si: 1.8wt%; Fe: 0.2wt%; Ti: 0.2wt%; the balance is Al; The mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The preparation method of the mesoporous titanium dioxide fiber comprises the following steps: S11. The solvent ethanol, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are mixed and stirred uniformly, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:15:14:3, and a precursor solution is obtained; S12. The precursor solution was loaded into a syringe for electrospinning at a voltage of 20 kV, a spinning solution flow rate of 1.0 mL / h, a receiving distance of 15 cm, and a drum speed of 50 r / min to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 was calcined and kept warm at a temperature of 900° C. for 1 h to obtain a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The composition of the high entropy oxide ceramic nanoparticles is (Ni 0.2 Cr 0.2 Mg 0.2 Co 0.2 Y 0.2 )3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm. Comparative Example 5: An aluminum-based composite material, the aluminum-based composite material consisting of 85wt% aluminum alloy and 15wt% mesoporous titanium dioxide fiber; The preparation method of the aluminum-based composite material comprises the following steps: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered, the sintering pressure is 45MPa, the sintering temperature is 600°C, the holding time is 10min, the furnace is cooled to room temperature and then taken out to obtain an aluminum-based composite material; The aluminum alloy is composed of the following components in weight ratio: Zn: 5.9wt%; Mg: 2.6wt%; Cu: 1.7wt%; Si: 1.9wt%; Fe: 0.3wt%; Ti: 0.1wt%; the balance is Al; The mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The preparation method of the mesoporous titanium dioxide fiber comprises the following steps: S11. The solvent ethanol, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are mixed and stirred uniformly, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:10:11:2 to obtain a precursor solution; S12. The precursor solution was loaded into a syringe for electrospinning at a voltage of 20 kV, a spinning solution flow rate of 1.0 mL / h, a receiving distance of 15 cm, and a drum speed of 50 r / min to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 was calcined and kept warm at a temperature of 700° C. for 1 h to obtain a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The composition of the high entropy oxide ceramic nanoparticles is (Ni 0.2 Cr 0.2 Mg 0.2 Co 0.2 Y 0.2 )3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm. Comparative Example 6: An aluminum-based composite material, the aluminum-based composite material consisting of 85wt% aluminum alloy and 15wt% mesoporous titanium dioxide fiber; The preparation method of the aluminum-based composite material comprises the following steps: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered, the sintering pressure is 45MPa, the sintering temperature is 600°C, the holding time is 10min, the furnace is cooled to room temperature and then taken out to obtain an aluminum-based composite material; The aluminum alloy is composed of the following components in weight ratio: Zn: 5.8wt%; Mg: 2.7wt%; Cu: 1.7wt%; Si: 2.3wt%; Fe: 0.4wt%; Ti: 0.2wt%; the balance is Al; The mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The preparation method of the mesoporous titanium dioxide fiber comprises the following steps: S11. The solvent ethanol, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are mixed and stirred uniformly, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:10:11:2 to obtain a precursor solution; S12. The precursor solution was loaded into a syringe for electrospinning at a voltage of 20 kV, a spinning solution flow rate of 1.0 mL / h, a receiving distance of 15 cm, and a drum speed of 50 r / min to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 was calcined and kept warm at a temperature of 1000° C. for 1 h to obtain a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles; The composition of the high entropy oxide ceramic nanoparticles is (Ni 0.2 Cr 0.2 Mg 0.2 Co 0.2 Y 0.2 )3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm. Comparative Example 7: An aluminum-based composite material, the aluminum-based composite material consisting of 85wt% aluminum alloy and 15wt% mesoporous titanium dioxide fiber; The preparation method of the aluminum-based composite material comprises the following steps: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered, the sintering pressure is 45MPa, the sintering temperature is 600°C, the holding time is 10min, the furnace is cooled to room temperature and then taken out to obtain an aluminum-based composite material; The aluminum alloy is composed of the following components in weight ratio: Zn: 5.7wt%; Mg: 2.3wt%; Cu: 1.0wt%; Si: 1.8wt%; Fe: 0.1wt%; Ti: 0.1wt%; the balance is Al; The mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with metal oxide ceramic nanoparticles; The preparation method of the mesoporous titanium dioxide fiber comprises the following steps: S11. The solvent ethanol, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are mixed and stirred uniformly, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:10:11:2 to obtain a precursor solution; S12. The precursor solution was loaded into a syringe for electrospinning at a voltage of 20 kV, a spinning solution flow rate of 1.0 mL / h, a receiving distance of 15 cm, and a drum speed of 50 r / min to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 was calcined and kept warm at a temperature of 900°C for 1 h to obtain a mesoporous titanium dioxide fiber loaded with metal oxide ceramic nanoparticles; The composition of the oxide ceramic nanoparticles is (Ni 0.5 Y 0.5 )3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm. Table 4 Effect of high entropy oxide ceramic nanoparticle composition on the mechanical properties of composites Microhardness test, tensile test and bending test were carried out on each embodiment and comparative example, and the results are shown in Tables 1-4. In summary, each embodiment of the present invention has high strength and hardness, and has a higher elongation at break. Compared with the comparative example, the comprehensive mechanical properties are excellent.

Claims

1. A mesoporous titanium dioxide fiber reinforced aluminum matrix composite material, characterized in that: The aluminum-based composite material consists of 85-95wt% of aluminum alloy and 5-15wt% of mesoporous titanium dioxide fibers.

2. The method for preparing the mesoporous titanium dioxide fiber reinforced aluminum-based composite material according to claim 1, characterized in that: The following steps are involved: S1. The aluminum alloy powder and the mesoporous titanium dioxide fiber are prepared in proportion, placed in a ball mill and evacuated, and ball milled to mix evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the powder and fiber to obtain a pre-pressed green body; S3. Place the green body into a plasma discharge sintering furnace, pressurize and evacuate, heat up for sintering and keep warm, take it out after the furnace cools to room temperature, and obtain a mesoporous titanium dioxide fiber reinforced aluminum-based composite material.

3. The method for preparing the mesoporous titanium dioxide fiber reinforced aluminum-based composite material according to claim 2, characterized in that: The sintering pressure in step S3 is 35-45 MPa, the sintering temperature is 550-600° C., and the holding time is 10-20 min.

4. The mesoporous titanium dioxide fiber reinforced aluminum matrix composite material according to claim 1, characterized in that: The aluminum alloy comprises the following components in weight ratio: composition: Zn: 5.5-6.0wt%; Mg: 2.2~2.8wt%; Cu: 1.0~1.8wt%; Si: 1.5~2.5wt%; Fe: ≤0.4wt%; Ti: ≤0.2wt%; the balance is Al.

5. The mesoporous titanium dioxide fiber reinforced aluminum matrix composite material according to claim 1, characterized in that: The mesoporous titanium dioxide fiber is a mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles.

6. The mesoporous titanium dioxide fiber reinforced aluminum matrix composite material according to claim 1, characterized in that: The preparation method of the mesoporous titanium dioxide fiber comprises the following steps: S11. The ethanol solvent, the template agent polyvinyl pyridine, the titanium source titanyl sulfate and the hydrolysis inhibitor acetic acid are prepared in proportion and stirred to obtain a precursor solution; S12. The precursor solution is loaded into a syringe, and the process parameters are adjusted for electrospinning to obtain a precursor fiber; S13. Dissolve each metal nitrate in a deionized water-ethanol solution in proportion and stir thoroughly to obtain a uniform solution; S14. The precursor fiber prepared in S12 is placed in the solution prepared in S13, and an ammonia solution is added and stirred. After sufficient reaction, the fiber is filtered to obtain a fiber loaded with a precipitate; S15. The fiber prepared in S14 is calcined and kept warm to obtain mesoporous titanium dioxide fiber loaded with high entropy oxide ceramic nanoparticles.

7. The mesoporous titanium dioxide fiber reinforced aluminum matrix composite material according to claim 6, characterized in that: In the step S11, the mass ratio of ethanol, polyvinyl pyridine, titanyl sulfate and acetic acid is 100:8-12:10-12:2-3.

8. The mesoporous titanium dioxide fiber reinforced aluminum matrix composite material according to claim 6, characterized in that: The electrospinning voltage of step S22 is 18-22 kV, the spinning solution flow rate is 0.8-1.2 mL / h, the receiving distance is 13-17 cm, and the drum speed is 45-55 r / min.

9. The method according to claim 6, characterized in that Mesoporous titanium dioxide fiber reinforced aluminum-based composite material: the calcination temperature in step S15 is 800-900° C., and the insulation time is 1-2 hours.

10. The mesoporous titanium dioxide fiber reinforced aluminum matrix composite material according to claim 1, characterized in that: The composition of the high entropy oxide ceramic nanoparticles is (Ni 0.15-0.25 Cr 0.15-0.25 Mg 0.15-0.25 Co 0.15-0.25 Y 0.15-0.25 )3O4, the particle size range is 50-150nm, the diameter of the mesoporous titanium dioxide fiber is 5-7μm, the length is 50-100μm, and the mesopore diameter is 20-60nm.